Pembuatan Protokol Penapisan Virtual Berbasis Stuktur (pvbs) untuk Identifikasi Ligan Inhibitor Reseptor Platelet-Activating Factor (PAF-r) sebagai Target Terapeutik Asma menggunakan YASARA - Nugraha, Gerry; Istyastono, Enade Perdana (Universitas Andalas, 2020)
Platelet-activating factor receptors (PAF-r) is known as one of the receptors that affect asthma, while the Y-21480 ligand is reported as an effective, specific, and active PAF-r antagonist for asthma patients. Research in building structure-based virtual screening protocol (SBVS) for identification of PAF-r ligand inhibitors has been performed, the receptor crystal structure was obtained from the Protein Data Bank (PDB ID: 5zkp), while the ligand used as a leading compound is Y-24180, obtained from U.S. National Library of Medicine. Interactions between ligands and receptors are observed through molecular dynamics simulations using the YASARA program at intervals up to 20 nanoseconds, ligand-receptor binding stability occurs after a time interval of 2 nanoseconds, the lowest ligand-receptor binding energy occurs at a time interval of 1,401 picoseconds. Internal validation by re-docking 1,000 times the ligand to receptor resulted in a value of Root Mean Square Deviation (RMSD) of 0.6037 Ã…,Â confirmed that SBVS protocol was accurately able to reproduce the Y-24180 ligand pose on the 5zkp crystal structure,Â the protocol can be used as a new approach for investigation or design of compounds that have therapeutic potential as anti-asthma.